Bibliometric Analysis of Trends in Theory-related Policy Publications - Zahra, Abitassha Az; Nurmandi, Achmad; Tenario, Christine B.; Rahayu, Riska; Benectitos, Samantha Herector; Mina, Faye Lorraine P.; Haictin, Ken M. (Emerging Science Journal, 2021)
This study's bibliometric analysis evaluates the scope and trends of theory-related policy publications in various international journals. The method used the Scopus search engine on random journals in identifying policy-related publications. The study also used a data visualization software called VOSviewer to analyze the results, underlying network linkages, and information production trends in policy analysis. The findings shows that only a few proportions of policy-related researches apply theories in their study. Field-specialized journals were having practitioners publish less research as compared to interdisciplinary science and technology journals. This article calls for greater engagements among scholars, and for policy researchers to more explicitly consider how their work might contribute to the understanding of the policy challenges. The findings also shows that it is important to recognize the approach and theory behind policy development to determine the incremental nature of aspects involved in policy development. It is extremely valuable to be clear that if one deals only with conceptual level of policy research without testing those ideas against independent empirical information, then scientific theory development is not possible. Thus, failure to consistently and clearly make theory connection towards policy research is a lost opportunity for scholars to influence policy thinking and public argument.Â Doi: 10.28991/esj-2021-01261 Full Text: PDF